Long-term neurological and psychiatric outcomes in patients with aromatic l-amino acid decarboxylase deficiency. (October 2022) - Manti, Filippo; Mastrangelo, Mario; Battini, Roberta; Carducci, Claudia; Spagnoli, Carlotta; Fusco, Carlo; Tolve, Manuela; Carducci, Carla; Leuzzi, Vincenzo
Abstract: Introduction: l -amino acid decarboxylase deficiency (AADCD) is an ultrarare autosomal recessive defect of biogenic amine synthesis that presents with early-onset encephalopathy progressing to severe neurological impairment and intellectual disability. We aimed to explore neurocognitive and behavioral profiles associated with AADCD and possible factors predicting outcome in more detail. Methods: Nine AADCD patients (23.2 ± 10.3 years; range 8–40) underwent systematic clinical and neuropsychological assessment. Diagnostic levels of CSF 5-hydroxyindolacetic acid (5-HIAA) and homovanillic acid (HVA), and DDC genotype (as ascertained by American College of Medical Genetics and Genomics grading) were included in the data analysis. Results: All AADCD patients were affected by intellectual disability and psychiatric disorders. Movement disorders included parkinsonism-dystonia, dysarthria, and oculogyric crises. CSF 5-HIAA and HVA levels at diagnosis had a significant influence on adaptive behavior and executive function performance. Patients homozygous for DDC pathogenetic variants showed lower CSF 5-HIAA and HVA levels and higher Unified Parkinson's Disease Rating Scale scores. The disease showed a self-limiting clinical course with partial improvement under pharmacological treatment (B6 and dopamine mimetic drugs). Conclusions: Patients with AADCD suffer from neuropsychological and psychopathological impairment, which may be improved but not reversed under the present therapeutic approach. However, cognitive functioning should be specifically examined in order to avoid its underestimation on the basis of movement disorder severity. Genotype and biogenic amine level at diagnosis have an important prognostic value. Highlights: AADC deficiency results in a severe neurodevelopmental disorder. Specific profile of neurocognitive and behavioral impairment is associated with AADCD. Genotype and the severity of neurotransmitter depletion predict clinical outcome.